ETHICAL DILEMMAS AND MORAL FRAMEWORKS: NAVIGATING THE INTEGRATION OF ARTIFICIAL INTELLIGENCE IN ISLAMIC SOCIETIES - Indah Rahayu; Handrini Ardiyanti; Loso Judijanto; A. Hamid; Eyad Saleh Bani-Domi (Adisam Publisher, 2023)
In Islamic societies, integrating artificial intelligence (AI) poses significant ethical dilemmas, necessitating a careful navigation of moral frameworks. This abstract encapsulates the essence of a comprehensive exploration of these intricate dynamics. As AI technologies advance and permeate various aspects of society, the ethical considerations surrounding their adoption become increasingly paramount. In the specific context of Islamic societies, where cultural, religious, and ethical values play a central role in daily life, the integration of AI introduces a complex interplay between innovation and tradition. This study delves into the ethical dilemmas inherent to AI deployment in Islamic societies, examining data privacy, autonomy, accountability, and bias. To navigate these ethical quandaries, it is essential to consider the moral frameworks embedded in Islamic ethics and jurisprudence. The study explores how Islamic principles, including justice, compassion, and ethical responsibility, can guide the development and deployment of AI technologies. Furthermore, it investigates the compatibility and potential tensions between contemporary AI ethics and Islamic moral values. Through a multidisciplinary lens, encompassing fields such as computer science, ethics, theology, and law, this research oflers a nuanced understanding of the ethical challenges posed by AI in Islamic societies. It aims to contribute to the ongoing discourse on responsible AI integration while preserving the moral fabric of Islamic traditions.